P32 Are junior doctors safe to perform pleural procedures? An audit of junior doctor knowledge and competency of pleural procedures before and after dedicated lecture-based and practical teaching sessions. (2nd December 2011) - Ruickbie, S V; MacDonald, G; Walters, N; Draper, A; Ong, Y E
Abstract : Introduction: Pleural procedures are considered core competencies at the end of ST2 medical training but with the advent of sub-specialisation within medicine and reduced working hours, junior doctors may have less exposure to these procedures. Aims and Objectives: One of the major themes that arose from the 2008 Rapid Response Report was inexperienced doctors undertaking procedures. We sought to determine the level of knowledge and competency at pleural procedures of junior doctors (F1-ST2) before and after teaching sessions to assess whether improvement occurred. Methods: Junior doctors were asked to complete a questionnaire in early 2011 about their self-assessed level of competency at pleural procedures and testing knowledge on various aspects of chest drain insertion and removal. A series of lectures at "mandatory" teaching days and optional practical drain insertion sessions on animal cadavers were delivered and junior doctors were asked to repeat the questionnaire between June and July 2011. Results: 57 doctors filled in the questionnaire pre-teaching and 37 completed in after teaching. Please see Abstract P32 table 1 for results. On re-audit, some of the most concerning findings were that 1 out of the 5 ST2 trainees had performed <3 thoracocentesis and 3 out of the 5 had performed <3 Seldinger chest drain insertion (1 never performed procedure) just prior to the completion of their ST2 rotation. Conclusion: Dedicated teaching covering all aspects tested in the questionnaire led to an improvement in theoretical knowledge about pleural procedures but worrying basic deficiencies remain. It is uncertain whether the trainees had not attended teaching or had not absorbed the information. In addition junior doctors still perform relatively few pleural procedures. Of particular concern, some ST2s who are shortly to be medical SpRs have performed very few pleural procedures which are part of their core competency. Whether this is due to lack of opportunity due to reduction in hours or other factors is uncertain. This may represent a significant risk for patients presenting out of hours who require an emergency pleural procedure.